Awareness and utilization of smoking cessation clinics in Saudi Arabia, findings from the 2019 Global Adult Tobacco Survey - Sarah S. Monshi; Abdullah M. M. Alanazi; Ali M. Alzahrani; Abdulrhman A. Alzhrani; Turky J. Arbaein; Khulud K. Alharbi; Mansour Z. Alqahtani; Ali H. Alzahrani; Ahmed A. Elkhobby; Aljoharah M. Almazrou; Abdulmohsen H. Al-Zalabani (Substance Abuse Treatment, Prevention, and Policy, 2023)
Abstract Background Tobacco use remains a leading cause of premature death. To combat tobacco use, the Ministry of Health (MOH) improved access to smoking cessation clinics (SCCs) by developing fixed SCCs and mobile SCCs, which move based on demand across locations. The goal of this study was to investigate awareness and utilization of SCCs among tobacco users in Saudi Arabia and the factors that influence their awareness and utilization. Method This cross-sectional study used the 2019 Global Adult Tobacco Survey. Three outcome variables were employed, including tobacco users’ awareness of fixed SCCs, mobile SCCs, and utilization of fixed SCCs. Several independent variables were examined, including sociodemographic characteristics and tobacco use. Multivariable logistic regression analyses were performed. Results One thousand six hundred sixty-seven tobacco users were included in this study. There were 60%, 26%, and 9% of tobacco users who were aware of fixed SCCs, aware of mobile SCCs, and visited fixed SCCs, respectively. The likelihood of being aware of SCCs increased among users residing in urban areas (fixed SCCs: OR = 1.88; 95% CI = 1.31–2.68; mobile SCCs: OR = 2.09; CI = 1.37–3.17) while it decreased among those reported self-employed (fixed SCCs: OR = 0.31; CI = 0.17–0.56; mobile SCCs: OR = 0.42; CI = 0.20–0.89). The likelihood of visiting fixed SCCs increased among educated tobacco users aged 25–34 (OR = 5.61; CI = 1.73–18.21) and 35–44 (OR = 4.22; CI = 1.07–16.64) while the odds of visiting SCCs decreased among those who were working in the private sector (OR = 0.26; CI = 0.09–0.73). Conclusion The decision to quit smoking must be supported by an effective healthcare system that provides accessible and affordable smoking cessation services. Knowing the factors that influence the awareness and utilization of SCCs would help policymakers dedicate efforts targeting those who desire to quit smoking yet face limitations in using SCCs.